The African American encounter with Japan and China : Black internationalism in Asia, 1895-1945 - Gallicchio, Marc, 1954- (University of North Carolina Press, 2000)
Focusing on African-American attitudes towards China and Japan, this study examines the rise and fall of black internationalism. The failed quest for support, the author argues, foretold the difficulty black society would encounter in seeking redress for American racism in the international arena.